Robust Synthesis of Gold Cubic Nanoframes through a Combination of Galvanic Replacement, Gold Deposition, and Silver Dealloying. Issue 18 (4th March 2013) - Wan, Dehui; Xia, Xiaohu; Wang, Yucai; Xia, Younan
Abstract A facile, robust approach to the synthesis of Au cubic nanoframes is described. The synthesis involves three major steps: 1) preparation of Au–Ag alloyed nanocages using a galvanic replacement reaction between Ag nanocubes and HAuCl4; 2) deposition of thin layers of pure Au onto the surfaces of the nanocages by reducing HAuCl4 with ascorbic acid, and; 3) formation of Au cubic nanoframes through a dealloying process with HAuCl4. The key to the formation of Au cubic nanoframes is to coat the surfaces of the Au–Ag nanocages with sufficiently thick layers of Au before they are dealloyed. The Au layer could prevent the skeleton of a nanocage from being fragmented during the dealloying step. The as‐prepared Au cubic nanoframes exhibit tunable localized surface plasmon resonance peaks in the near‐infrared region, but with much lower Ag content as compared with the initial Au–Ag nanocages.